Contacts Between the ‘Amuq and Syria-Palestine - Tadmor, Miriam
ersch. 1965; Review art of R. J. Braidwood – I,. J. Braidwood, Excavations in the Plain of Antioch. I. The Earlier Assemblages, Phases A-J. (OIP 61, Chicago 1960).